Identification of the Key Regulators of Spina Bifida Through Graph-Theoretical Approach - Tamkeen, Naaila; AlOmar, Suliman Yousef; Alqahtani, Saeed Awad M.; Al-jurayyan, Abdullah; Farooqui, Anam; Tazyeen, Safia; Ahmad, Nadeem; Ishrat, Romana (Frontiers in Genetics, 2021)
Spina Bifida (SB) is a congenital spinal cord malformation. Efforts to discern the key regulators (KRs) of the Spina Bifida (SB) protein-protein interaction (PPI) network are requisite for developing its successful interventions. The architecture of the SB network, constructed from 117 manually curated genes was found to self-organize into a scale-free fractal state having a weak hierarchical organization. We identified three modules/motifs consisting of ten KRs, namely, TNIP1, TNF, TRAF1, TNRC6B, KMT2C, KMT2D, NCOA3, TRDMT1, DICER1, and HDAC1. These KRs serve as the backbone of the network, they propagate signals through the different hierarchical levels of the network to conserve the network’s stability while maintaining low popularity in the network. We also observed that the SB network exhibits a rich-club organization, the formation of which is attributed to our key regulators also except for TNIP1 and TRDMT1. The KRs that were found to ally with each other and emerge in the same motif, open up a new dimension of research of studying these KRs together. Owing to the multiple etiology and mechanisms of SB, a combination of several biomarkers is expected to have higher diagnostic accuracy for SB as compared to using a single biomarker. So, if all the KRs present in a single module/motif are targeted together, they can serve as biomarkers for the diagnosis of SB. Our study puts forward some novel SB related genes that need further experimental validation to be considered as reliable future biomarkers and therapeutic targets.